A New Radiocarbon Database for the Lower 48 States. Issue 3 (July 2022) - Kelly, Robert L.; Mackie, Madeline E.; Robinson, Erick; Meyer, Jack; Berry, Michael; Boulanger, Matthew; Codding, Brian F.; Freeman, Jacob; Garland, Carey James; Gingerich, Joseph; Hard, Robert; Haug, James; et al.
Abstract : From 2014 to 2020, we compiled radiocarbon ages from the lower 48 states, creating a database of more than 100, 000 archaeological, geological, and paleontological ages that will be freely available to researchers through the Canadian Archaeological Radiocarbon Database. Here, we discuss the process used to compile ages, general characteristics of the database, and lessons learned from this exercise in "big data" compilation.